Comprehensive landscape-style investigation of the molecular mechanism of acupuncture at ST36 single acupoint on different systemic diseases - Xiaojing Fan; Yunlong Liu; Shanshan Li; Yongrui Yang; Yinghui Zhao; Wenxi Li; Jiaxin Hao; Zhifang Xu; Bo Zhang; Wei Liu; Suzhao Zhang (Heliyon, 2024)
The principle of acupoint stimulation efficacy is based on traditional meridian theory. However, the molecular mechanisms underlying the therapeutic effects of acupoints in treating diseases remain unclear in modern scientific understanding. In this study, we selected the ST36 acupoint for investigation and summarized all relevant literature from the PubMed database over the past 10 years. The results indicate that stimulation of ST36 single acupoints has therapeutic effects mainly in models of respiratory, neurological, digestive, endocrine and immune system diseases. And it can affect the inflammatory state, oxidative stress, respiratory mucus secretion, intestinal flora, immune cell function, neurotransmitter transmission, hormone secretion, the network of Interstitial Cells of Cajal (ICC) and glucose metabolism of the organism in these pathological states. Among them, acupuncture at the ST36 single point has the most prominent function in regulating the inflammatory state, which can mainly affect the activation of MAPK signaling pathway and drive the ''molecular-cellular'' mode involving macrophages, T-lymphocytes, mast cells (MCs) and neuroglial cells as the core to trigger the molecular level changes of the acupuncture point locally or in the target organ tissues, thereby establishing a multi-system, multi-target, multi-level molecular regulating mechanism. This article provides a comprehensive summary and discussion of the molecular mechanisms and effects of acupuncture at the ST36 acupoint, laying the groundwork for future in-depth research on acupuncture point theory.